Analysis Michael E Porter's Generic Strategy on Increasing Furniture Products Sales - Ramadania, Devi Fitriani; Dharma, Budi (Management Department Universitas Islam Negeri Sumatera Utara, 2023)
In times of economic instability, such as when the Covid-19 pandemic spreads in Indonesia, furniture companies need the right strategy to compete. Increasing sales during these conditions takes work; therefore, a fairly effective strategy is required through the three-point strategy coined by Michael E Porter, namely cost leadership, differentiation, and focus. This research aims to find a generic strategy suitable for implementation at PT. Home Center Indonesia Retail Informa branch Warung Jambu Bogor. The author chose the in-depth interview research method as a qualitative descriptive analysis technique. They were guided by Michael E Porter's generic strategy theory, namely cost leadership strategy, differentiation strategy, and focus strategy, as a tool to analyze this research. The results of the research conducted by the author concluded that the focus strategy had more influence on increasing sales of PT. Home Center Indonesia Retail Informa branch Warung Jambu Bogor.Keywords: Focus Strategy, Generic Strategy, Increasing Sales, Sales Innovation.